Strategy of the Indonesian Waqf Agency, North Sumatra Representative Office in Increasing the National Waqf Index - Muslim Marpaung; Irma Suryani Lubis (LPPM Universitas Terbuka, 2024)
The long-term objective of the research is to design a recommended model for the Indonesian waqf Board in North Sumatra so that it can be applied to improve the national waqf index in North Sumatra. The success of this model can be measured by the achievement of the National Waqf Index value of North Sumatra Province. The specific target of this research is to improve the understanding of the national waqf index indicators of BWI and in North Sumatra, to identify obstacles, and to determine actions that must be taken. This research produces mandatory outputs of the Model recommended to BWI North Sumatra regarding the steps in filling out the National Waqf Index (IWN) and Simple Patents and Additional Outputs of Sinta Accredited Journals. This research uses a qualitative method with data collection techniques through observation and interviews, where the research team will conduct interviews with BWI Representatives of North Sumatra Province, BWI representatives of districts and cities throughout North Sumatra, and waqf stakeholders and requires a cost of Rp. 10,500,000 (Ten Million Five Hundred Thousand Rupiah).